2019
DOI: 10.23917/jramathedu.v4i1.6972
|View full text |Cite
|
Sign up to set email alerts
|

Students' Mathematical Communication Ability through the Brain-Based Learning Approach using Autograph

Abstract: AStudents’ skills in expressing mathematical ideas in various ways have not met the expectation. Teachers need to apply the learning providing students’ opportunities to present their mathematical ideas. Utilizing the Brain-Based Learning (BBL) approach with Autograph can help students develop their mathematical communication skills. The purpose of this study was to analyze the development of students’ mathematical communication skills. Twenty-eight 10th grade students in one of the high schools in Banda Aceh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 9 publications
1
9
0
8
Order By: Relevance
“…Mathematical communication skills after using the Autograph (disugraph) learning media have increased, in other words, the Autograph learning media has a positive influence on mathematical communication skills. This is supported by the findings of Triana, Zubainur & Bahrun [14] and Chasanah, Riyadi & Usodo [20], namely the study showed that mathematics learning applying BBL approach with Autograph contributes to developing students' mathematical communication skills. From the test results of mathematical communication skills between before and after using the Autograph learning media (disugraph), respectively, the maximum value is 70, the minimum value is 25, the average is 47.88, the standard deviation is 11.112 and the maximum value is 75, the minimum value is 35, average 52.73, standard deviation 9.445.…”
Section: B Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Mathematical communication skills after using the Autograph (disugraph) learning media have increased, in other words, the Autograph learning media has a positive influence on mathematical communication skills. This is supported by the findings of Triana, Zubainur & Bahrun [14] and Chasanah, Riyadi & Usodo [20], namely the study showed that mathematics learning applying BBL approach with Autograph contributes to developing students' mathematical communication skills. From the test results of mathematical communication skills between before and after using the Autograph learning media (disugraph), respectively, the maximum value is 70, the minimum value is 25, the average is 47.88, the standard deviation is 11.112 and the maximum value is 75, the minimum value is 35, average 52.73, standard deviation 9.445.…”
Section: B Discussionsupporting
confidence: 68%
“…The essence of these two studies is that there must be unusual strategies to improve students' communication skills. Mathematical communication skills are still far from expectations according to Triana, Zubainur & Bahrun [14] who said Students' skills in expressing mathematical ideas in various ways had not met the expectation. He found that using the Brain-Based Learning (BBL) approach with Autograph can help students develop mathematical communication skills.…”
Section: Introductionmentioning
confidence: 94%
“…Pasifnya mahasiswa mengungkapkan gagasan yang dimiliki diantaranya diakibatkan mahasiswa takut gagasan yang disampaikan salah. Hal ini sesuai dengan penelitian yang dilakukan oleh (Triana et al, 2019), keterampilan siswa dalam mengungkapkan ide matematika dengan berbagai cara belum sesuai dengan harapan. Banyak siswa masih kesulitan dalam mengemukakan pendapatnya.…”
Section: Pendahuluanunclassified
“…Komunikasi adalah proses penyampaian informasi, ide, emosi, dan keterampilan melalui penggunaan simbol seperti kata-kata, gambar, angka, dan lainnya (Viseu & Oliveira, 2012;Triana, & Zubainur, 2019). Selanjutnya, Hirsche & Cotton (2008) menyatakan bahwa komunikasi matematika membantu dalam membangun makna ketika peserta didik melakukan proses berpikir dan bernalar, lalu mengomunikasikan ide matematis mereka secara lisan maupun tulisan sehingga pemahaman konsep berkembang.…”
Section: Pendahuluanunclassified